Bacteriological profile and antibiogram of surgical site infection/ post-operative wound infection - Budhani, Diksha; Kumar, Surinder; Sayal, Pallavi; Singh, Sanjeet (International Journal of Medical Research and Review, 2016)
Background: Surgical site infections (SSI) constitute a major public health problem worldwide and are the second most frequently reported as Nosocomial infections. Surgical site infections are responsible for increasing the treatment cost, length of hospital stay and significant morbidity and mortality. Objectives: Bacteriological profile and antibiogram of Surgical Site Infection /Post-operative wound infection and to find drug useful for empirical treatment. Material and Methods: The retrospective study was conducted for a period of one year (January 2015 to Dec 2015) in the Department of Microbiology of BPSGMC Khanpur Kalan, Sonepat, Haryana.Samples were collected using sterile cotton swabs. 1687 patients clinically diagnosed of having SSIs were processed as per standard microbiological techniques. Antimicrobial susceptibility testing was done using modified Kirby-Bauer disc diffusion method. Results: Among 1687 patients screened for SSIs, 971 (57.5%) were culture positive. Staphylococcus aureus (25.5%) was the commonest organism followed by Escherichia coli (23.5%), Citrobacter species (17.3%) and Pseudomonas aeruginosa (9.9%). Antimicrobial profile of gram positive isolates revealed maximum sensitivity to Linezolid and Vancomycin, whereas among gram negative isolates Imipenem, Gentamicin, Piperacillin-Tazobactam, and Amikacin were found to be most sensitive. Conclusion: Staphylococcus aureus was the commonest pathogen isolated followed by E.coli (23.5%). Imipenem, Piperacillin/ Tazobactum, Gentamicin and Amikacin can be used as empirical treatment for gram negative bacilli and for gram positive organism Vancomycin and Linezolid can be used as empirical treatment in patients with Surgical Site Infection